Ponovna relevantnost jugoslovanske družbeno angažirane otroške književnosti z antifašistično in antiimperialistično noto - Burcar, Lilijana (Slavistična revija, 2025)
Drawing on historical materialism and new historicism, the article problematises the lack of socially engaged children’s literature in our region after 1990, specifically literature dedicated to fostering geopolitical awareness among children as readers. In the context of the new imperialist re-division of the world and the dangerous spread of armed conflicts, the rekindling of the Yugoslav heritage of children’s anti-fascist and anti-imperialist literature is again urgently needed in our region. Anticolonial literature is a way of realigning children with reality. It offers them necessary critical insights and cultivates social awareness so that they will strive for peace as children today and as adults tomorrow.
Keywords: literarna kritika; literarna zgodovina; literary criticism; literary history; Slovene literature; slovenska književnost